Effects of Substrate and Annealing Conditions on the Ferroelectric Properties of Non-Doped HfO2 Deposited by RF Plasma Sputter - Lim, Seokwon; Ahn, Yeonghwan; Won, Beomho; Lee, Suwan; Park, Hayoung; Kumar, Mohit; Seo, Hyungtak (Nanomaterials, 2024)
In this study, the effect of annealing and substrate conditions on the ferroelectricity of undoped hafnium oxide (HfO2) was analyzed. Hafnium oxide was deposited on various substrates such as platinum, titanium nitride, and silicon (Pt, TiN, Si) through RF magnetron sputtering. Annealing was performed in a nitrogen atmosphere at temperatures ranging from 400 to 600 °C, and the process lasted anywhere from 1 to 30 min. As a result, it was confirmed that the orthorhombic phase, the main cause of ferroelectricity, was dominant after a post-anneal at 600 °C for 30 min. Additionally, it was observed that interface mixing between hafnium oxide and the substrate may degrade ferroelectricity. Accordingly, the highest remanent polarization, measured at 14.24 μC/cm2, was observed with the Pt electrode. This finding was further corroborated by piezo force microscopy and endurance tests, with the results being significant compared to previously reported values. This analysis demonstrates that optimizing substrate and annealing conditions, rather than doping, can enhance the ferroelectricity of hafnium oxide, laying the foundation for the future development of ferroelectric-based transistors.
Keywords: ferroelectricity; hafnium oxide; orthorhombic; sputtering; substrate